Evaluation of Extractants and Critical Limits of Sulphur for Rapeseed in Acid Soils of Assam - and N.G. Barua, B. Rajkonwar, A. Basumatary (Journal of the Indian Society of Soil Science, 2016)
A pot experiment was conducted with twenty four soils of varying characteristics for selecting the most suitable chemical extractant for available sulphur (S) and determination of the critical limits of S for rapeseed (var. TS-38). The average dry matter yield increased significantly with increasing levels of S application. In terms of the efficiency of extraction, the extractants were in the order: Ca(H2PO4)2.H2O > KH2PO4> NH4OAc > Morgan’s reagent> 0.15% CaCl2> 1% NaCl> Bray-1. Available S extracted by 0.15% CaCl2 showed the highest correlation with Bray’s per cent yield (r= 0.820**), Bray’s per cent uptake (r= 0.840**), absolute yield (r= 0.796**) and absolute uptake (r= 0.813**). Therefore, this extractant was rated as most promising extractant for assessing S availability for rapeseed in acid soils of Assam. The critical level of available soil S was 10.50 mg kg-1 and the critical S concentration in rapeseed plant was 0.15% at 60 days growth.